Enhanced adsorption of sulfamethoxazole from aqueous solution by Fe-impregnated graphited biochar. (20th May 2020) - Zhang, Runyuan; Zheng, Xiaoxian; Chen, Bohan; Ma, Jinlin; Niu, Xiaojun; Zhang, Dongqing; Lin, Zhang; Fu, Mingli; Zhou, Shaoqi
Abstract: An increasing amount of antibiotics has been released into the aquatic environment and caused a serious threat to public health. In this study, a series of magnetic biochars (MBCs) were prepared via one-step graphitization and magnetization for sulfamethoxazole (SMX) removal. The effects of pyrolysis temperature and impregnated FeCl3 concentration on SMX adsorption were investigated. Characterization of MBC were carried out through SEM, BET, XRD, FTIR, Raman and XPS analyses. The performance for sulfamethoxazole removal was evaluated with the adsorption kinetics and isotherms studies, and the influence of pH, temperature, ion and NOM on SMX adsorption capacity was also examined in batch studies. The results show that the physicochemical properties of the MBCs were dominated by the pyrolysis temperatures and the iron weight ratio. The iron species in MBCs contributed significantly to the enhancement of SMX adsorptive capacity, including increasing the carbonization degree, promoting the formation of oxygen-rich functional groups and providing more adsorption sites. The prepared MBCs was proved to be highly efficient for SMX removal, and the 300-MBC800 was the optimal sorbent with the maximum adsorption capacity of 187.31 mg g −1, which was 5.3 times of the pristine biochar. The primary mechanisms for SMX adsorption include electrostatic interaction, π-π electron-donor-acceptor (EDA) interaction, hydrogen bonding, and Lewis acid-base electron interactions, mainly resulting from the graphitized structures and enriched functional groups on MBCs. This study demonstrated promise of MBC as an effective and environmentally friendly sorbent for removing SMX from wastewater with high adsorption capacity and cost effectiveness. Graphical abstract: Image 1 Highlights: Higher temperature and iron weight ratio increased the graphitized degree of MBC. Iron spices on MBC promoted the formation of oxygen-rich functional groups. The MBCs exhibited a superb sulfamethoxazole adsorption capacity up to 205 mg g −1 . Hydrogen bonding and π-π EDA interactions were the dominant adsorption mechanisms. The MBCs exhibited highly real-water applicable for sulfamethoxazole removal.